Patents as indicators for knowledge generation and diffusion in mechanical engineering and green biotechnology: A first assessment - Peter Neuhäusler; Rainer Frietsch (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
This study includes two expert reports, which are based on each other. At the core of the first expertise is the analysis of the patent application structures within the technological field of mechanical engineering and their evolution over time at an international level. Secondly, building on the first expertise, a field comparison of mechanical engineering and green biotechnology is performed with the help of a patent analysis.
urn:nbn:de:0011-n-2649016
Keywords: 330